Kreuzspiel: Für oboe, bassklarinette, klavier, 3 schlagzeuger - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 2010)
Dress rehearsal, introduction and concert of KREUZSPIEL conducted by Stockhausen( Colour film by Suzanne Stephens ) ( Archive No. 27 / 12 )Dress rehearsal and performance of KREUZSPIEL with introduction, Alte Oper Frankfurt,August 23rd 1992 with Ensemble Modern conducted by Karlheinz Stockhausen.